IL-10 Protects Mice From the Lung Infection of Acinetobacter baumannii and Contributes to Bacterial Clearance by Regulating STAT3-Mediated MARCO Expression in Macrophages - Kang, Min-Jung; Jang, Ah-Ra; Park, Ji-Yeon; Ahn, Jae-Hun; Lee, Tae-Sung; Kim, Dong-Yeon; Lee, Moo-Seung; Hwang, Seungwoo; Jeong, Yu-Jin; Park, Jong-Hwan (Frontiers in Immunology, 2020)
Interleukin-10 plays important, yet contrasting, roles in host protection against bacterial infections and in the septic response. To determine the role of IL-10 in the host defense against Acinetobacter baumannii infection, wild-type (WT) and IL-10-deficient mice were infected intranasally with the bacteria. IL-10-deficient mice exhibited increased mortality, severe pathology, and excess production of proinflammatory cytokines and chemokines in the lungs, and increased bacterial burdens in bronchoalveolar lavage (BAL) fluids and lung homogenates after A. baumannii infection, compared to WT mice. Intranasal administration of recombinant IL-10 rescued mice from the lethality of the bacterial infection by promoting bacterial clearance and reducing production of cytokines and chemokines in the lungs. In vitro experiments revealed that IL-10 enhanced phagocytosis and bacterial killing by macrophages by upregulating the macrophage receptor with collagenous structure (MARCO). In addition, A. baumannii-induced activation of STAT3 was impaired in IL-10-deficient macrophages, which was essential for expression of MARCO. Intranasal adoptive transfer of WT macrophages resulted in significant increases in mice survival and bacterial clearance in IL-10-deficient mice infected with A. baumannii. Our results show that IL-10 played an important role in the host defense against pulmonary infection of A. baumannii by promoting the antibacterial function of macrophages by regulating MARCO expression through the STAT3-mediated pathway.